How Indonesians Cope with Chronic Pain: Does Seeking Help and Comfort from God Work? - Gozan, Muthmainah Mufidah; Asih, Sali Rahadi (Psychological Research on Urban Society, 2021)
Chronic pain is a significant health problem in many countries including Indonesia, with high prevalence and the possibility to increase in the future. Individuals experiencing chronic pain elicit cognitive and behavioral responses, including pain catastrophizing which can cause high pain interference. Effective coping ability can help reduce the impact of pain catastrophizing on pain interference. Previous research focused on emotion-focused and problem-focused coping in dealing with chronic pain. However, Indonesia as a country with a strong influence from religious values and practices encourages the exploration of positive religious coping. A part of a longitudinal study on psychological factors in chronic pain development, this study aimed to examine the moderating role of three coping styles on pain catastrophizing and pain interference associations. Results from 368 participants male and female with chronic pain showed that positive religious coping and problem-focused coping significantly moderated the effects of pain catastrophizing on pain interference. Seeking help from God helped individuals deal with chronic pain problems, as well as actively resolving difficulties. The use of these two coping styles in the Indonesian population can be useful for managing chronic pain.